2014
DOI: 10.1109/jsee.2014.00111
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual design and RCS performance research of shipborne early warning aircraft

Abstract: In order to improve the survivability of the aircraft, conceptual design and radar cross section (RCS) performance research are done. The CATIA software is used to design the 3D digital model of the shipborne early warning aircraft, and some measures are taken to reduce the RCS characteristics of the early warning aircraft at the same time. Based on the physical optics method and the equivalent electromagnetic ow method, the aircraft's RCS characteristics and strength distribution characteristics are simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…is the dot product and "×" is the cross product; j: imaginary unit, and j 2 = 1; λ: incident wavelength, in m; : strength of the incident magnetic field; r t : position vector of the middle of the edge; l: vector of the edge; θ: angle between i and t. Other symbols' definition can be found in Yue et al (2014aYue et al ( , 2014cYue et al ( , 2014dYue et al ( , 2015.…”
Section: Rcs Prediction Methodsmentioning
confidence: 99%
“…is the dot product and "×" is the cross product; j: imaginary unit, and j 2 = 1; λ: incident wavelength, in m; : strength of the incident magnetic field; r t : position vector of the middle of the edge; l: vector of the edge; θ: angle between i and t. Other symbols' definition can be found in Yue et al (2014aYue et al ( , 2014cYue et al ( , 2014dYue et al ( , 2015.…”
Section: Rcs Prediction Methodsmentioning
confidence: 99%
“…The RCS characteristics of the models are numerically simulated in the self-compiled software RCSAnsys [15,16] under the conditions of incoming wave pitch angle from -10° to +10° and X radar band and H-H polarization based on 4 …”
Section: Numerical Simulation Of the Rcs Characteristics Of The Protomentioning
confidence: 99%
“…The stealth performances and aerodynamic characteristics of a conceptually designed aircraft are discussed in reference [14]. A stealth embarked early warning aircraft and an electronic warfare aircraft are conceptually designed and discussed in reference [15] and reference [16] respectively. In reference [17], an aircraft of variable-sweep wings is conceptually designed and the stealth performance of the aircraft is studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies successfully showed the aircraft RCS study using the high-frequency methods [15]- [22]. The SBR method was used to analyze the RCS of various aircrafts including scale down models [15]- [17] and full-scale models [16]- [19], which were assumed as a perfect electric conductor (PEC). In addition, the RCS of aircrafts full- [20] and partially coated [21], [22] with radar absorbing materials (RAM) was evaluated using the SBR method.…”
Section: Introductionmentioning
confidence: 99%